Association between dietary glycine intake and the prevalence of hypertension, hyperlipidemia, overweight or obesity in rural northern China: a cross-sectional study - Feng, Ying; Gu, Xing-bo; Zhou, Meng; Wang, Hong-lan; Feng, Ren-nan; Zhang, Zhi-hong (Frontiers in Nutrition, 2024)
Objective: The objective of this research is to investigate the relationship between dietary glycine consumption and the prevalence of hypertension, hyperlipidemia, and overweight or obesity in economically disadvantaged areas of northern China using a cross-sectional study design.A cross-sectional study involving 774 participants utilized a web-based dietary questionnaire (IDQC) and underwent physical measurements. Data analysis was conducted using IBM SPSS Statistics software (Version 21). Participants were stratified into four groups based on quartiles of their dietary glycine intake: Q1 (<1.32), Q2 (1.32-1.82), Q3 (1.82-2.26), and Q4 (>2.26). Continuous variables were reported as mean ± standard deviation and compared using ANOVA or the Kruskal-Wallis test, while categorical variables were presented as frequencies (%) and compared using the chi-square test. Finally, multivariable logistic regression with p-value of less than 0.05 was considered statistically significant.Results: Significant differences in dietary glycine intake were observed between the highest quartile group (Q4) and the lowest quartile group (Q1), with corresponding dominance ratios of 0.590 (95% CI, 0.360-0.966), 0.547 (95% CI, 0.327-0.913), and 0.547 (95% CI, 0.353-0.850) for the risk of hypertension, hyperlipidemia, and overweight/obesity, respectively. Furthermore, no significant correlation was found between dietary glycine intake and hypertension or hyperlipidemia within each sex and age subgroup.There exists a potential correlation between increased dietary glycine intake and reduced prevalence of hypertension, hyperlipidemia, and overweight/obesity. However, additional research is necessary to validate this finding through larger-scale studies conducted at a population level.